A study of the experience of China in opening up the higher education market and Vietnam’s experience with policy mechanisms to encourage foreign investment and cooperation - Dang, Thi Thao (International research journal of management, IT and social sciences, 2024)
International joint training plays a very important role in the effort to improve the quality of the education sector, thereby enhancing the prestige and status of the industry and the nation. In recent times, departments and universities have continuously strengthened their expansion efforts, seeking the best partners and cooperation opportunities to enhance the effectiveness of managing international joint training programs. In addition to the achievements in enhancing management capacity, there are still many limitations. Therefore, thoroughly researching and evaluating the experiences of some countries in international joint training activities, and subsequently proposing appropriate solutions for the next phase, especially regarding policies to promote cooperation and foreign investment, is one of the urgent requirements for higher education in Vietnam.